Planning, Implementation, and Evaluation of Problem-Based Learning in Improving Students' Critical Thinking Skills on History Subjects - Wilujeng, Nuruz Tri; Widodo, J. Priyanto; Wibowo, Satrio (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
This research explores the implementation of Problem-Based Learning (PBL) model in history learning at SMA Kemala Bhayangkari 3 Porong and evaluates its effectiveness in improving students' critical thinking skills. Qualitative research method was used with data from observation, interview, and document analysis in class XI 5. The result of this study shows that the lesson planning involves ATP and interesting Teaching Module, with PBL that encourages students to think critically through group discussion and presentation. Evaluation was conducted comprehensively. PBL effectively improves students' critical thinking skills and makes history learning more relevant and interesting. The implementation of Merdeka Curriculum with PBL creates a dynamic and student-centred learning atmosphere.